1983
DOI: 10.1063/1.94462
|View full text |Cite
|
Sign up to set email alerts
|

New types of high efficiency solar cells based on a-Si

Abstract: Three types of new structure a-Si solar cells having more than 9% efficiency are presented. The first one has a high optical reflection back electrode metal alloyed with optically transparent n-type μc-Si deposited on the conventional glass substrate a-SiC/a-Si heterojunction solar cell. The second type structure is an inverted p-i-n solar cell having Ag/TiO2/a-Si metal-insulator-semiconductor type back surface electrode which more efficiently collects longer wavelength photocarriers just above the band edge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…A few years later, intrinsic a-Si:H films were found to passivate c-Si surfaces remarkably well [30]. The first solar cell using a silicon heterojunction was reported in 1983 by Hamakawa and coworkers in the form of an a-Si:H/poly-Si heterojunction bottom cell in a tandem junction solar cell, the so-called Honeymoon cell [31,32]. At about the same time, the electronic junction between doped a-Si:H and c-Si was increasingly investigated [33,34].…”
Section: The Heterojunction Conceptmentioning
confidence: 99%
“…A few years later, intrinsic a-Si:H films were found to passivate c-Si surfaces remarkably well [30]. The first solar cell using a silicon heterojunction was reported in 1983 by Hamakawa and coworkers in the form of an a-Si:H/poly-Si heterojunction bottom cell in a tandem junction solar cell, the so-called Honeymoon cell [31,32]. At about the same time, the electronic junction between doped a-Si:H and c-Si was increasingly investigated [33,34].…”
Section: The Heterojunction Conceptmentioning
confidence: 99%
“…A buffer layer between the Si and SiC however can provide a proper , transition and as has been suggested, it may ease the strain between the two lattices, and good quality SiC single crystal growth -becomes possible (4,5,6). It has been found that a proper buffer "* layer can be formed at near 1400 0 C substrate temperature either by reaction with propane(4) or by sputtering SiC onto the Si surface(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, this application does not expose the cells to the continuous strong levels of sunlight and so the serious question of degradation remains to be answered by long term tests. Earlier cells, of about 3 % efficiency, appeared to be stable, but later improved cells showing commercial production efficiencies about twice as high appear to suffer some degradation, although it is claimed that the degradation becomes negligible after an initial decay (Hamakawa 1982;Hamakawa et al 1983). This property, along with others, is very sensitive to production procedures, since the manner of deposition of films onto heated substrates in a glow discharge is a complex and not well understood process.…”
Section: Amorphous Hydrogenated Siliconmentioning
confidence: 99%